Food Reciprocity and Sustainability in Early Childhood Care and Education in Aotearoa New Zealand. (13th January 2015) - Ritchie, Jenny; Leahy, Deana; Gray, Emily; Cutter-Mackenzie, Amy; Eames, Chris
Abstract This article offers a perspective from early childhood care and education in Aotearoa New Zealand. It draws from the data of four recent studies to demonstrate pedagogical practices informed by Indigenous (Māori) perspectives. Māori values, such as manaakitanga (caring, hospitality, generosity) and whanaungatanga (relatedness), are shown featuring in routines focused on provision of food and serving as a key focus of early childhood education for sustainability. It is argued that providing opportunities for children to become engaged with growing, cooking and sharing food enables them to operationalise compassion towards themselves, others and the environment, reconnecting with the source of their food and demonstrating generosity and care to others (both human and more-than-human) in their communities. This can be viewed as a pedagogical response to the increasing encroachment of neoliberalism, with its incumbent individualism and lack of collectivist consciousness or concern for the environment, into education settings. Furthermore, drawing upon Indigenous perspectives honours traditional, localised wisdom regarding sustainability practices.